ANALISIS MANAJEMEN REKAM MEDIS DI PUSKESMAS SOREANG KABUPATEN BANDUNG - Laili, Ayu (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2024)
Background: The recapitulation of the percentage of incomplete filling in medical record files at the Soreang Community Health Center, Bandung Regency in 2019 was 52.13%, causing delays in the orderly administration process, inaccurate patient clinical data, making it difficult for other health workers to take action, and reporting being hampered. Objective: This research aims to determine how medical record management is implemented at the Soreang Community Health Center. Method: In this type of qualitative descriptive research, the number of informants in this study was 5 people, namely the head of the community health center, head of administration, medical records officer, doctor, and nurse in charge of carrying out medical record management activities. Data collection techniques and methods use interview guidelines, observation, and document review. Results: The research results show that medical record management at the Soreang Community Health Center needs to be supported starting from input consisting of man, money, material, machines, and methods. In contrast, the process consists of patient registration, assembling, coding, indexing, filing, and retention, thereby producing Output namely the orderly management of medical records. Conclusion: there is still low compliance among health workers in filling out medical records, delays in funding, there is no tracer controlling medical records, and standard operating procedures (SOP) have not been fully implemented in an orderly manner. The suggestion for managing medical records is to increase monitoring, evaluation, and enforcement of discipline and compliance for officers to increase the completeness of medical record data files at the Soreang Community Health Center.